The combination of IL-2 nanoparticles and Palbociclib enhances the anti-tumor immune response for colon cancer therapy - Wang, Di; Wang, Xiaoshuang; Zhang, Yingyu; Yu, Le; An, Jing; Wang, Xiaodong; Huang, Yue; Han, Xuemei (Frontiers in Immunology, 2024)
Immunotherapy of tumors plays a pivotal role in the current treatment of cancer. While interleukin 2 (IL-2) demonstrated its efficacy as an immunotherapeutic drug in the early days, its short blood circulation time poses challenges in maintaining effective therapeutic concentrations. Additionally, IL-2's activation of regulatory T cells can counteract its anti-cancer effects. Therefore, the primary goal of this study was to formulate IL-2-carrying nanoparticles via boron-nitrogen coordination between methoxy poly (ethylene glycol) block poly-[(N-2-hydroxyethyl)aspartamide ]phenylboronic acid (mPEG-b-PHEA-PBA, P-PBA) and poly (L-lysine) (PLL). These nanoparticles are intended to be used in combination with CDK4/6 inhibitors to address the short blood circulation time of IL-2, reduce its immunosuppressive effects, and enhance the overall immune response. The envisaged outcome is a sustained and potent therapeutic effect, offering a novel and promising combination therapy strategy for tumor immunotherapy.